Experience in Treating Patients with The Consequences of Facial Burns (Eurasian Scientific Herald, 2023)
The article describes the developed algorithm of surgical treatment of patients with postburn scar deformities of the face. Facial burns can cause serious damage to the skin, soft tissues, and even the bones of the face. This can lead to long-term physical limitations, impaired sensory functions, as well as problems with breathing and swallowing. It is advisable, after the healing of burn wounds of the face, first of all, the elimination of scar microstomy. The next step is to eliminate eyelid inversions and scarring of the nostrils. After that, plastic surgery should be performed locally in stages to eliminate cicatricial deformities of soft tissues of other parts of the face. The study of the long-term results showed the effectiveness and correctness of the algorithm we developed. Practical recommendations are given.